Integration in Chinese E-Commerce and Public Policy Concerns: An Analysis of Alibaba Group - Qin, Peipei (Thammasat Review of Economic and Social Policy, 2017)
Established in 1999, Alibaba’s market value reached 231 billion USD in 2004. Taobao.com, including Tmall.com, is Alibaba’s consumer-to-consumer portal. In March 2013, the combined gross merchandise volume (GMV) of Taobao and Tmall exceeded 1 trillion CNY. Alibaba Group has developed its own third party payment – Alipay, based on big data analysis – to ensure a safe and clear payment environment for the privacy concerning customers. The logistics industry bonds with online sales tightly. A number of logistics companies seize the opportunity and gain benefits from the booming sales volume. This paper aims to explore the integration of e-commerce, third party payment, and the logistics industry. However, besides the prodigious development of those industries, they have their own limitations. This paper analyzes the limitation of Taobao.com, Alipay, and the logistics industry as well as the dilemma they are facing. Important public policy concerns are discussed accordingly.